Mímesis and Prâxis: Republic I, II, III and X - Vecchio, Ariel (2022)
This paper presents an updated reading of the Platonic confrontation of Republic I, II, III and X with poets. Specifically, opposing the traditional readings that tend to focus on the ontological plane, this writing will investigate the Platonic warning about the plasticity and, consequently, the functionality of images. It is proposed as a contribution to redirect the criticism of poets to one of the central topics of Rep., the tension between appearance and reality, to account for their connection with the forms of (self)deception in. In this sense, the objective is to show that the capacity of myths to form character and the social imaginary, as a dispositive of power, is anchored in the types of access and the ways of knowing that guide. This will then allow us to rethink a current topic: The capacity of, in a broad sense, to produce subjects and social values, as well as the ways of practical knowledge.